Case study of the adoption of open innovation in Brazilian public entities - Izycki, Luís (Revista del CLAD Reforma y Democracia, 2025)
Technological evolution has triggered significant social changes, with the rise of emerging technologies such as blockchain and the advancement of artificial intelligence reshaping production processes and social interactions. Faced with these transformations, the State faces the need for rapid and innovative responses to meet society’s demands, promoting inclusion and quality of public services. Thus, open innovation emerges as a strategic approach that encourages collaboration between public and private organizations, universities, startups and other actors, in order to drive sustainable economic and social development. In the public sector, this approach can contribute to the formulation of more effective policies and the provision of higher quality services by involving citizens and other stakeholders in the decision-making process. This strengthens the legitimacy of public institutions, while maximizing the impact of investments in innovation. In this context, this article presents a case study on the opportunities and challenges of assimilating emerging technologies by the National School of Public Administration together with other public entities through open innovation. This article is a case study on the opportunities and challenges of assimilating emerging technologies by the National School of Public Administration together with other public entities through open innovation.